ELIMINATION OF LOSSES USED LEAN MANUFACTURING TECHNIQUES AND KAIZEN PHILOSOPHY - Andrei DIMITRESCU; Ana-Maria ALECUSAN; Claudiu BABIS; Elisabeta NICULAE (BANICA); Loredana DASCALU (Fiabilitate şi Durabilitate)
Lean manufacturing is today one of the most successful production strategies for improving competitiveness. To achieve success, a healthy production system based on solid concepts and philosophies is also required. Thus, it has been decided to adopt and accelerate the Lean Manufacturing concept on every site. The Kaizen or "Continuous Improvement by Involving All" method is a teamwork methodology used to systematically solve problems and apply improvement solutions.